THE EFFECT OF OVER DIMENSION OVERLOAD (ODOL) VEHICLES ON NATIONAL ROAD DAMAGE - Nurkhowati, Nurul; Widodo, Slamet; Kadarini, Siti Nurlaily (Jurnal Teknik Sipil, 2023)
The road's condition owing to the vehicle's Over Dimension Over Load (ODOL) is one of several highway issues. To further supervise and conduct road safety against overload as stated in Law No. 22 of 2009 concerning Road Traffic and Transportation article 169 paragraph (1) to (3), it is necessary to research to determine the extent to which Over Dimensions Over Load (ODOL) vehicles affect the life of the road plan on the flexible pavement. This article discusses the Effect Of Over Dimension Overload (Odol) Vehicles On National Road Damage in Kalimantan Barat, specifically on the Jalan Lintas Kalimantan Poros Tengah/Jalan Raya Sosok II Kabupaten Sanggau and as a comparison in selected Jalan Raya Sintang, Kabupaten Sintang. This study examines the impact of Over Dimension Over Load (ODOL) cars on the VDF (Vehicle Damage Factor) and the 2023 ZERO ODOL plan on the pavement plan for the Jalan Lintas Kalimantan Poros Tengah (Jalan Raya Sosok II Kabupaten Sanggau and Jalan Raya Sintang, Kabupaten Sintang), a national route in Kalimantan Barat.By using primary data (photo documentation of dimension overload vehicles, road conditions) and secondary data (average daily traffic from P2JN, ODOL percentage data from BPTD XIV West Kalimantan, vehicle data at UPPKB Sosok and UPPKB Sintang, the calculation of traffic growth, vehicle overload, vehicle damage factor (VDF) value due to ODOL vehicles, Equivalent Single Axle Load, plan CESA, normal CESA, overload CESA, and remaining life (RL) value).The investigation shows that Jalan Raya Sosok II Kabupaten Sanggau and Jalan Raya Sintang, Kabupaten Sintang's plant life cannot survive owing to the vehicle's Over Dimension Over Load (ODOL). Jalan Raya Sosok II Kabupaten Sanggau will last 8.04 years and Jalan Raya Sintang, Kabupaten Sintang 8.23 years. Thus, Jalan Raya Sosok II Kabupaten Sanggau 1, 95 years or 19.5%, and Jalan Raya Sintang, Kabupaten Sintang 1, 77 years or 17.7%, have shorter pavement lifespans.